2022
DOI: 10.1029/2021jb022489
|View full text |Cite
|
Sign up to set email alerts
|

ANU GRACE Data Analysis: Orbit Modeling, Regularization and Inter‐satellite Range Acceleration Observations

Abstract: Small changes in the strength of the Earth's gravity field caused by the redistribution of mass on the Earth cause subtle changes in the range between the satellites. This is the fundamental observation that made the grace mission unique.A number of different mathematical approaches have been used to parameterize the Earth's gravity field and the convergence of the inversions of the data. Solving for coefficients of spherical harmonic models has been the most common approach used since the start of the grace m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…It is the range acceleration prefit residuals that were used as our inter-satellite observable when estimating the temporal gravity field. In our companion paper (Allgeyer et al, 2022), we demonstrated that using range acceleration information in this manner leads to a reduction in north/south striping in estimated gravity fields while also being able to spatially resolve both the low-and high-frequency components of the temporal gravity field.…”
Section: Temporal Gravity Field Estimationmentioning
confidence: 91%
See 4 more Smart Citations
“…It is the range acceleration prefit residuals that were used as our inter-satellite observable when estimating the temporal gravity field. In our companion paper (Allgeyer et al, 2022), we demonstrated that using range acceleration information in this manner leads to a reduction in north/south striping in estimated gravity fields while also being able to spatially resolve both the low-and high-frequency components of the temporal gravity field.…”
Section: Temporal Gravity Field Estimationmentioning
confidence: 91%
“…No perturbations were applied to any of these satellite parameters in the simulations. We solved for adjustments to the initial satellite positions/velocities, accelerometer calibration scale factors and biases (one per axis per satellite per day), and adjustments to the mascons in terms of an equivalent height of water (of the appropriate density) in a least squares inversion of our simulated observations for each month (Allgeyer et al, 2022):…”
Section: Temporal Gravity Field Estimationmentioning
confidence: 99%
See 3 more Smart Citations